Ekonomiczno-Społeczne zagadnienia sporu o powszechne uwłaszczenie - Suwalski, Andrzej (Wydział Prawa i Administracji UAM, 1997)
The article presents dilemmas arising from the idea of distribution of shares of state - owned companies to all citizens (universal privatisation). It examines the relationship between this concept of universal privatisation and the Universal Privatisation Scheme currently implemented in Poland. The article presents also how this concept has taken shape. Subsequently the questions asked in the privatisation referenda of February 18, 1996 are being discussed. In conclusion the article analyses the possible impact of including some ideas of universal privatisation into the general course of transformation of the Polish economy.
Economic and social espects of a debate about universal privatization